2017
DOI: 10.1093/infdis/jix567
|View full text |Cite
|
Sign up to set email alerts
|

Formula Feeding Predisposes Neonatal Piglets to Clostridium difficile Gut Infection

Abstract: Spontaneous outbreaks of Clostridium difficile infection (CDI) occur in neonatal piglets, but the predisposing factors are largely not known. To study the conditions for C. difficile colonization and CDI development, 48 neonatal piglets were moved into isolators, fed bovine milk-based formula, and infected with C. difficile 078. Analyses included clinical scoring; measurement of the fecal C. difficile burden, toxin B level, and calprotectin level; and postmortem histopathological analysis of colon specimens. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 45 publications
4
30
0
Order By: Relevance
“…We have recently demonstrated that neonatal piglets fed a formula milk develop gut symptoms similar to that observed in CDI piglets and they also show lower expression of TJ proteins, as compared to suckling piglets [8]. Moreover, neonatal piglets that are switched to formula feeding are known to develop gut microbial dysbiosis, which may predispose them to CDI [8,29]. Our findings as well as previous data clearly support the importance of porcine milk including colostrum in offspring nutrition as a gut barrier for protection against CDI.…”
Section: Discussionmentioning
confidence: 75%
See 4 more Smart Citations
“…We have recently demonstrated that neonatal piglets fed a formula milk develop gut symptoms similar to that observed in CDI piglets and they also show lower expression of TJ proteins, as compared to suckling piglets [8]. Moreover, neonatal piglets that are switched to formula feeding are known to develop gut microbial dysbiosis, which may predispose them to CDI [8,29]. Our findings as well as previous data clearly support the importance of porcine milk including colostrum in offspring nutrition as a gut barrier for protection against CDI.…”
Section: Discussionmentioning
confidence: 75%
“…Furthermore, C. difficile toxins have been reported to mediate acute inflammation by induction of microtubule depolymerisation in human colonocytes and induce a pro-inflammatory response in an experimental piglet model [7,28]. We have recently demonstrated that neonatal piglets fed a formula milk develop gut symptoms similar to that observed in CDI piglets and they also show lower expression of TJ proteins, as compared to suckling piglets [8]. Moreover, neonatal piglets that are switched to formula feeding are known to develop gut microbial dysbiosis, which may predispose them to CDI [8,29].…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations